Effects of anti‐thrombotic drugs on all‐cause mortality after upper gastrointestinal bleeding in Japan: A multicenter study with 2205 cases. Issue 1 (1st April 2021) - Matsuhashi, Tamotsu; Fukuda, Sho; Mikami, Tatsuya; Tatsuta, Tetsuya; Hikichi, Takuto; Nakamura, Jun; Abe, Yasuhiko; Onozato, Yusuke; Hatta, Waku; Masamune, Atsushi; Ohyauchi, Motoki; Ito, Hirotaka; et al.
Abstract : Objects: Although anti‐thrombotic use is recognized as a risk factor for upper gastrointestinal bleeding (UGIB), there has been no clear evidence that it worsens the outcomes after the bleeding. The aim of this study is to investigate the effects of anti‐thrombotic agents on in‐hospital mortality following UGIB. Methods: Information on clinical parameters, including usage of anti‐thrombotic agents, was retrospectively collected from consecutive patients with UGIB at 12 high‐volume centers in Japan between 2011 and 2018. The all‐cause in‐hospital mortality rate was evaluated according to the usage of anti‐thrombotic agents. Results: Clinical data were collected from 2205 patients with endoscopically confirmed UGIB. Six hundred and forty‐five (29.3%) patients used anti‐thrombotic agents. The all‐cause in‐hospital mortality rate was 5.7% (125 deaths). After excluding 29 cases in which death occurred due to end‐stage malignancy, 96 deaths (bleeding‐related, n  = 22 ; non‐bleeding‐related, n  = 74) were considered "preventable." Overall, the "preventable" mortality rate in anti‐thrombotic users was significantly higher than that in non‐users (6.0% vs. 3.7%, P  < 0.05). However, the "preventable" mortality of anti‐thrombotic users showed a marked improvement over time; although the rate in users remained significantly higher than that in non‐users until 2015 (7.3% vs. 4.2%, P  < 0.05), after 2016, the difference was no longer statistically significant (4.8% vs. 3.5%). Conclusions: Although the usage of anti‐thrombotic agents worsened the outcomes after UGIB, the situation has recently been improving. We speculate that the recent revision of the Japanese guidelines on the management of anti‐thrombotic treatment after UGIB may have partly contributed to improving the survival of users of anti‐thrombotic agents.